1981
DOI: 10.1128/aac.19.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ceforanide as treatment for staphylococcal and streptococcal endocarditis

Abstract: Ceforanide administered parenterally twice daily was used as the sole agent to treat 17 patients with right-sided endocarditis due to Staphylococcus aureus or nonenterococcal streptococci. Fifteen patients were cured of their original infection. Two patients were withdrawn from the study. One patient was transferred to another hospital 4 days after ceforanide therapy was initiated, and the other was changed to a different antibiotic regimen when his viridans streptococcus proved tolerant to ceforanide. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The slower elimination of both of these drugs during bypass may have been due to the decrease in blood flow from this tissue since the site of the aorta selected for drug assay was below the level of the aortic clamp, or it may have been due to a reduction in the renal (6) 23.6 ± 6.4 (4) 41-60 19.5 ± 9.9 (4) 48.1 ± 3.7 (2) 21.5 ± 8.8 (3) 23.8 ± 8.5 (3) 24.3 (1) 22.5 ± 11.0 (3) 61-80 18.1 ± 6.9 (2) 11.3 ± 7.5 (3) 23.3 ± 1.8 (2) 81-100 9.1 (1) 40.8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slower elimination of both of these drugs during bypass may have been due to the decrease in blood flow from this tissue since the site of the aorta selected for drug assay was below the level of the aortic clamp, or it may have been due to a reduction in the renal (6) 23.6 ± 6.4 (4) 41-60 19.5 ± 9.9 (4) 48.1 ± 3.7 (2) 21.5 ± 8.8 (3) 23.8 ± 8.5 (3) 24.3 (1) 22.5 ± 11.0 (3) 61-80 18.1 ± 6.9 (2) 11.3 ± 7.5 (3) 23.3 ± 1.8 (2) 81-100 9.1 (1) 40.8…”
Section: Discussionmentioning
confidence: 99%
“…The results of an in vitro kinetic study (14) showed that the bactericidal activity of ceforanide was greater than the activity of cephalothin, cefazolin, cefamandole, cefuroxime, or cefoxitin. Moreover, ceforanide administered parenterally twice daily has been found to be an effective agent in the treatment of patients with right-sided endocarditis caused by S. aureus (3).…”
mentioning
confidence: 99%